Pang Pada Payu: Implementing Tri Hita Karana Principles on Pawongan Aspect as a Balinese Business Concept - Arsa, I. Ketut Sida; Mertanadi, I. Made; Widiastini, Ni Made Ary; Prayudi, Made Aristia (International Review of Management and Marketing, 2023)
Bali, as one of the renowned tourist destinations recognized globally, has led to the growth of various businesses, both those that support the development of tourism directly and through market chains. This qualitative descriptive research, which uses participatory observation and in-depth interviews, is conducted with the aim to understand, comprehend, and describe the implementation of the Tri Hita Karana principle in the pawongan aspect through one of Bali's local wisdoms, namely pang pada payu. A variety of business opportunities have grown and developed along with the rise of tourism in Bali. Apart from tourism, the high domestic sector needs to support cultural preservation have also experienced significant growth, regardless of the economic conditions. Balinese culture, as a tourism icon, in its implementation not only provides economic benefits for those in the tourism sector but also offers opportunities for businesses that play a role in meeting domestic needs. Various businesses that have grown in Bali not only give birth to competition but also present various forms of cooperation, known as pang pada payu. Pang pada payu is one of the local wisdoms possessed by the Balinese community that in its implementation resembles a market chain and is used as a guideline for conducting business.